Remote Learning Under the COVID-19 Social Distancing: Reflections and a Netnography Study - Nasu, Vitor Hideo (Journal of Information Systems and Technology Management, 2021)
The purpose of this work is two-fold. First, it intends to discuss and reflect on the transition from face-to-face to remote learning in accounting education because of the COVID-19 pandemic. And second, it presents the results of a netnography study conducted at the beginning of the COVID-19 outbreak in Brazil (March and April of 2020). I also provide some personal experiences during these times. In section 2, I provide key technology resources I found helpful for accounting instructors and students. In section 3, I discuss the implications for instructors and students brought by the COVID-19. I especially appreciate the effors that both instructors and students are doing to keep their academic lives going, despite all the adversity. In section 4, I describe a netnography study in which I examined data from a graduate students’ Facebook community. And in section 5, I report closing thoughts.